EFEKTIVITAS PERATURAN PEMERINTAH NOMOR 99 TAHUN 2012 DALAM PEMBERIAN REMISI KEPADA NARAPIDANA TINDAK PIDANA KHUSUS DI LEMBAGA PEMASYARAKATAN KLAS II A PADANG - Ab. Ghafur; Philips A. Kana; Wirna Rosmely (UNES Journal of Swara Justisia, 2018)
The reformation form of the imprisonment system established by the government is Law No. 12/1995 on Penalization. In the community system, the rights are given to human rights and the exercise of human rights, remission is the right of all prisoners of special crime is not easy to obtain such remission because it is contained in Article 34 A paragraph (1) because it is related to Government Regulation No. 99 of 2012 which determines the prerequisites to be met by the inmate can be said to be a constraint in the remission of the perpetrators of special criminal acts.This research is analytical descriptive with approach method used is normative juridical as main approach and supported by empirical juridical approach. Sources of data used are secondary data and primary data. The data obtained were analyzed qualitatively and presented analytically descriptively. Based on the discussion and analysis it can be concluded that the first obstacles encountered in the provision of remission to special prisoners of crime based on Government Regulation No. 99 of 2012 is the provision of remissions to convicts of special criminal offenses based on the discussion and analysis of the writer can be said not effective because the implementation of remission to convicts a special crime in Class II A Correctional Institution in Padang City is carried out in accordance with Article 34 of Government Regulation Number 99 of 2012 and 34 A Paragraph 1 of Regulation No. 99 of 2012 in addition to the process and procedure of granting remission is based on Regulation of Minister of Law and Ham Number 21 year 2013 on the procedure of giving Remission Asi milasi, Leave visiting family, Parole, Leave free, and Conditional leave. The effectiveness of giving remission to special prisoners based on Government Regulation No. 99 of 2012 has not run optimally since there are still obstacles, especially the coaching programs of Class II A Padang prison officers have not been fully accepted and can be fully implemented by prisoners.